Keefektifan Teknik Metafora Konseling Realita dalam Mereduksi Self-Blaming Siswa Akibat Korban Body Shaming - Kaesti, Mutiarani R. D. E; Aiwani, Aisyiah; Nate, Mahara Pinte; Hasanah, Binti Uswatun; Munir, Ah. Fahri; Fahira, Ihza Chaidaratul (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
Body shaming is a negative comment on a person's body shape, the impact caused by body shaming behavior is one of them on the victim of body shaming who is greatly harmed, resulting in self-blaming. It is important to have interventions for victims who feel self-blaming, so that they continue to grow in accordance with their developmental tasks optimally. The aim of this study was to determine the effectiveness of the reality counseling metaphor technique in reducing students' self-blaming as a result of being victims of body shaming. The research method uses the Systematic Literature Review. stematic Literature Review consists of several stages, namely formulating questions, searching for literature, establishing criteria, selecting literature, presenting data, processing data and drawing conclusions. The data obtained related to keywords is 19 articles. The articles were selected based on criteria close to the researchers' objectives, namely into 5 articles taken from 2015-2020. The results of this study based on previous literature reveal that the metaphorical technique using the reality counseling approach is effective for reducing students' self-blaming against victims of body shaming.